2012
DOI: 10.5402/2012/103714
|View full text |Cite
|
Sign up to set email alerts
|

Quick and Simple Evaluation of Sudomotor Function for Screening of Diabetic Neuropathy

Abstract: Objective. The aim of this study was to compare SUDOSCAN, a new device to evaluate sweat function (reflecting peripheral small C-fiber status), with conventional measures of peripheral and cardiac neuropathy in patients with type 2 diabetes. Methods. 265 diabetic patients were tested for symptoms and clinical signs of neuropathy using Michigan Neuropathy Screening Instrument (MNSI), vibration perception threshold (VPT) using biothesiometer, and cardiac autonomic neuropathy (CAN) using Ewing's protocol. Sudomot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
71
2
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(80 citation statements)
references
References 24 publications
(29 reference statements)
3
71
2
4
Order By: Relevance
“…Yajnik et al 25 evaluated different neuropathy assessments on 265 diabetes patients and found that ESC measurements between the left and right side varied by 9.5% for hands and 6.0% for feet, compared with 14.2% for the vibration perception threshold test. Lower measures of ESC were significantly associated with increasing symptoms on the Michigan Neuropathy Scoring Instrument A, which evaluates the presence of small and large fiber neuropathy symptoms; increasing physical abnormalities on the Michigan Neuropathy Scoring Instrument B, which includes feet inspection, vibration perception, ankle reflexes, and monofilament perception; and increasing scores on the vibration perception threshold test, reflecting impaired vibration perception.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yajnik et al 25 evaluated different neuropathy assessments on 265 diabetes patients and found that ESC measurements between the left and right side varied by 9.5% for hands and 6.0% for feet, compared with 14.2% for the vibration perception threshold test. Lower measures of ESC were significantly associated with increasing symptoms on the Michigan Neuropathy Scoring Instrument A, which evaluates the presence of small and large fiber neuropathy symptoms; increasing physical abnormalities on the Michigan Neuropathy Scoring Instrument B, which includes feet inspection, vibration perception, ankle reflexes, and monofilament perception; and increasing scores on the vibration perception threshold test, reflecting impaired vibration perception.…”
Section: Discussionmentioning
confidence: 99%
“…Lower ESC was specifically associated with postural fall in blood pressure, a measure of sympathetic cardiac autonomic neuropathy. 25 Mayaudon et al 8 measured sensitivity, specificity, and reproducibility of Sudoscan among 133 type 2 DM patients compared with 41 HCs. ESC showed a sensitivity of 75% and a specificity of 100%, with an area under the ROC curve of 0.88, similar to our current report.…”
Section: Discussionmentioning
confidence: 99%
“…As for the Sudoscan test, we used 60 μS of mean feet ESC as the cut‐off for diagnosis of DSPN according to previous studies18, 19.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, an algorithm that integrates ESC with age and BMI has been developed to produce a score estimating the individual's current risk of cardiac autonomic neuropathy (cardiac risk score). This risk score has been validated in several clinical studies10, 11, 12, 13, 14.…”
Section: Methodsmentioning
confidence: 99%